Diklat Pembuatan Media Evaluasi Pembelajaran Berbasis Game Edukasi (Wordwall) - Ashoumi, Hilyah; Hariono, Tholib; Hidayatulloh, Muhammad Kris Yuan; Fikroh, Faza Mufidatul; Setyaningsih, Irda; Qoyyimah, Maysarotud Dinul; Sanaya, Dini; Aulia, Sefindi (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
Education plays a crucial role in human life, as it allows individuals to develop their potential and solve various life challenges. According to the National Education System Law Number 20 of 2003, education aims to develop spiritual abilities, self-control, personality, intelligence, noble character, and the skills needed by individuals and society. However, the limited use of educational media often hinders the achievement of these educational goals, as observed in several educational institutions in the village of Asemgede. The use of lecture methods and minimal teaching aids have resulted in a lack of student enthusiasm for learning. To address this issue, the KKN team organized a training session on creating educational evaluation media using the Wordwall platform. This training aimed to enhance teachers' skills in creating interactive and engaging learning materials and to increase student participation and motivation. Wordwall offers various interactive games that can be used as tools for learning evaluation, which have proven effective in increasing student engagement. The results of the training showed that teachers in Asemgede village were enthusiastic about learning and implementing Wordwall in their teaching practices. Although there were some technical challenges, overall, the training successfully improved the teachers' creativity in evaluating students and stimulated students' enthusiasm for learning. The use of Wordwall media is expected to be further developed in the learning process to improve the quality of education in Asemgede village.